Effect of Transcutaneous Electrical Acupoint Stimulation on Red Blood Cell and Hemoglobin in College Athletes with Exercise Fatigue - Shijing YOU; Feng JI; Furong HE; Boying TONG (康复学报)
Objective:To observe the effect of transcutaneous electrical acupoint stimulation (TEAS) on the red blood cell (RBC) and Hemoglobin (Hb) in college athletes with exercise fatigue.Methods:A total of 45 male college athletes were assigned to the treatment group 1, the treatment group 2 and the control group by a random number table, and 15 athletes in each group. Three groups received intensive training for two weeks, and the treatment group 1 and the treatment group 2 received TEAS one hour before exercise and one hour after exercise. The control group did not receive any intervene. The physical subjective feelings were evaluated in each group and the contents of RBC and Hb were detected in 24 hours after intensive training for two weeks and before the training.Results:After the training, the values of physical subjective feelings were increased in the three groups (P<0.01, P<0.05), and the value in the treatment group 1, the treatment group 2 was lower respectively than that of the control group (P<0.05). After the training, the contents of RBC and Hb were decreased in the three groups (P<0.01, P<0.05), and the contents in the treatment group 1, the treatment group 2 were higher respectively than those of the control group (P<0.05).Conclusion:TEAS can improve the state of fatigue and enhance the ability of aerobic exercise via preventing the decrease of RBC and Hb contents..